The Impact of the Effectiveness of Fertilizer Subsidy Policy Implementation on the Technical Efficiency of Corn Farmers in Pamekasan Regency - Adjie Manggala Syahriyanda; elys fauziyah; Dwi Ratna Hidayati; Firman Farid Muhsoni; Meria Zakiyah Alfisuma; Sitti Aida Adha Taridala (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The fertilizer subsidy policy is a government program aimed at providing affordable fertilizer to enhance the productivity of domestic commodities, including corn. In 2022, there was a change in the fertilizer subsidy policy, specifically a reduction in the number of subsidized fertilizer types and commodities. This policy change caused farmers to bear higher production costs. In addition, the decline in corn productivity at the research site serves as an indicator of the ineffectiveness of the fertilizer subsidy policy implementation and a source of production inefficiency. This study aims to evaluate the effectiveness of the 2022 fertilizer subsidy policy implementation and analyze its impact on the technical efficiency of corn farming. The research was conducted in Kadur Subdistrict, Pamekasan Regency, East Java. The study employed a survey method involving 43 farmers who were selected using a purposive sampling technique. Data analysis was performed using a quantitative descriptive approach, incorporating effectiveness analysis and technical efficiency measurement through the Cobb–Douglas Stochastic Frontier production function. The findings indicate that the effectiveness of the 2022 fertilizer subsidy policy implementation falls within the “highly effective” category. Furthermore, improving the effectiveness of non-Farmer Card (non-Kartu Tani) usage and the distribution of subsidized fertilizers significantly enhances technical efficiency.